MANAJEMEN KEGIATAN EKSTRAKURIKULER UNTUK MENINGKATKAN BAKAT SISWA DI MTsN 5 HULU SUNGAI UTARA - Al Musa; M. Zuhdi; M. Aldi; Jamil Ihsan Muhsinin; Syahrani Syahrani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Extracurricular activities are activities carried out outside class hours which must be well developed by a madrasah, so that students' interests, talents and potential can be developed more optimally. In its implementation, management functions are needed, namely planning, implementation and evaluation so that extracurricular activities run effectively. Extracurricular activities are a forum for students who have talents or students who want to improve their talents. Extracurricular activities can help develop self-potential in student achievement. With extracurricular management, it will produce achievements in non-academic fields. Mtsn 5 Hulu Sungai Utara is one of the madrasas that has produced many students with non-academic achievements through extracurricular activities.